Influence of melengesterol acetate (MGA®) and Implus-H® implants on rate of gain, feed efficiency, and carcass characteristics of culled beef cows fed a high concentrate ration - M.F. Spire; J.C. Galland; John A. Unruh; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1998)
No statistical differences were detected in feedlot performance or carcass traits between control culled beef cows and those that were treated with melengesterol acetate (MGA®) and/or Implus-H® when fed in a feedyard for 56 days before slaughter. All groups performed well, indicating that this practice may be used to improve the market value of culled cows. Cow health during the feeding period is a major concern.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Culled cows; Melengesterol acetate; Implus-H implant; Feedlot health; Carcasses